Antioxidant Capacity And Physicochemical Properties Of Green Tea As Influenced By Types Of Brewing Water - Lee, Le Xuan (Universiti Sains Malaysia, 2021)
In this study, premium and standard grades from two different brands (TWG 1837 Green Tea and Lipton Pure Green Tea) of green tea were evaluated and comparatively analysed which were individually brewed with tap water (TP), alkaline ionized water (AK), magnetized water (MG), and mineral water (MN). The colour (L*, a*, b*and ho), pH, oxidation-reduction potential, total soluble solids, mineral content, and antioxidant properties (Total Phenolic Content (TPC), Flavonoid Content (FC) and DPPH scavenging assay) were used as parameters to examine the influence of brewing water and the brand of green tea.